2014
DOI: 10.4314/jmbs.v3i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and haematological changes following an acute toxicity study of a hydro-ethanolic whole plant extract of <i>Synedrella nodiflora</i> (L) Gaertn in male Sprague-Dawley rats

Abstract: Synedrella nodiflora (L) Gaertn (family Asteraceae), a common weed in Ghana, is traditionally used for the management of epilepsy, hiccup and threatened abortion. To further promote the ethnopharmacological uses of the plant, an acute toxicity of a hydro-ethanolic whole plant extract was assessed in male Sprague-Dawley rats. The lethal dose (LD50) and effects of a single oral administration of the extract (1600, 3200 and 6400 mg kg -1 ) on haematological and serum biochemical parameters were measured. The extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Synedrella nodiflora (L.) Gaertn, which is a member of Asteraceae family, is a widely distributed tropical plant species having potentials as medicinal plant (Adjei et al, 2014;Amoateng et al, 2017;Amoateng et al, 2012;Bhogaonkar et al, 2011;Dutta, et al, 2012;Islam et al, 2013;Rathi & Gopalakrishnan, 2006), bioinsecticide (Belmain et al, 2001) and detoxificant for heavy metals such as Cu and Pb (Prekeyi & Oghenekevwe, 2007). On the other hands, it is also commonly found as broad-leaf weed in several crops, particularly in legumes, causing severe impacts with respect of productivity (Hasanudin et al, 2012;Moenandir et al, 1996;Murrinie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Synedrella nodiflora (L.) Gaertn, which is a member of Asteraceae family, is a widely distributed tropical plant species having potentials as medicinal plant (Adjei et al, 2014;Amoateng et al, 2017;Amoateng et al, 2012;Bhogaonkar et al, 2011;Dutta, et al, 2012;Islam et al, 2013;Rathi & Gopalakrishnan, 2006), bioinsecticide (Belmain et al, 2001) and detoxificant for heavy metals such as Cu and Pb (Prekeyi & Oghenekevwe, 2007). On the other hands, it is also commonly found as broad-leaf weed in several crops, particularly in legumes, causing severe impacts with respect of productivity (Hasanudin et al, 2012;Moenandir et al, 1996;Murrinie, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated anticonvulsant (Amoateng et al, 2012), analgesic (Woode et al, 2009;Amoateng et al, 2015) and antioxidant effects (Amoateng et al, 2011) of the hydroethanolic extract of this plant, validating its traditional medicinal use. In addition, acute, sub-acute and sub-chronic toxicological investigations of the extract reveal minimal or no observable toxicity in rats (Adjei, et al, 2014a;Adjei, et al, 2014b;Amoateng et al, 2016). The in vivo models used for the anticonvulsant studies were chemically and electrically induced seizures in rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…The hydro-ethanolic extract of the whole plant has demonstrated anticonvulsant [ 13 ], sedative [ 14 ], in vitro antioxidant and free radical scavenging properties [ 15 ] as well as anti-nociceptive properties in acute and neuropathic pain [ 16 , 17 ]. An acute, sub-acute and sub-chronic toxicity of the extract in rodents showed no significant changes in haematological, biochemical and organ histological changes of animals treated with an LD 50 greater than 6400 mg/kg [ 18 – 20 ]. Our preliminary work conducted on this extract revealed that it was able to reduce stereotypic behaviour characteristic of schizophrenia and other psychotic conditions in experimental animals suggesting that it may have utility in the management of psychotic conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%